The challenge of assessing the state of exploitation of short-lived fishery resources with limited data: the blue shrimp (Penaeus stylirostris) fishery in the Gulf of California, Mexico - Arreguín-Sánchez, Francisco; Pérez-Quiñónez, Carlos Iván; Hernández-López, Armando; Chávez-Herrera, Darío (Frontiers in Marine Science, 2023)
Assessing the state of exploitation of a resource is key to its management. In the fishery of the blue shrimp, Penaeus stylirostris, off the central-eastern coast of the Gulf of Baja California, this assessment process is critical for two reasons: the data is limited because only catch and effort data are available, and the dynamic biomass model is not applicable to short-lived (annual) species. In this study, a procedure based on the Leslie model was used, and applied to the last 15 annual fishing seasons (2006 to 2021). Estimates of the monthly biomass per fishing season, the corresponding harvest rates (HRy), and indicators for the survival ratio, sy, representing the remaining stock at the end of the fishing season (essentially spawners), and the fishery’s recruitment rate, ρy, at the beginning of the fishing season, were obtained. These last two quantities, sy and ρy, were related to identify a limit biological reference point that reflects the replacement level for the shrimp stock, defined here as the limit for population renewal rate, PRRLim. Initially, a Kobe diagram was constructed based on HRy and sy, which indicated a sustainable fishery status that requires management measures to limit fishing to keep it sustainable, which is currently being implemented. A Kobe diagram was also constructed based on ρy, instead of sy, yielding the same results. Additionally, we used Kobe’s diagrams to show the contribution of the environment and an ecosystem-based reference point.